Nickel ion release and surface analyses on instrument fragments fractured beyond the apex: a laboratory investigation - Sıdıka Mine Toker; Ekim Onur Orhan; Arzu Beklen (BMC, 2023)
Abstract Background To analyse the changes in surface and nickel ion release characteristics of fractured root canal shaping instruments in a simulated body fluid environment. Methods A total of 54 new instruments were studied. The instrument groups consisted of five different NiTi alloys and a stainless-steel alloy. To standardize instrument fracture, a torsional type of failure was created on each instrument. The fractured specimens of each instrument group were randomly divided into three static immersion subgroups of 1 h, 7-day, and 30-day (n = 3). Simulated body fluid (SBF) was prepared to mimic human blood plasma by Kokubo&Takadama protocol for ex situ static immersions at 37ºC. The surfaces were examined via scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy. To determine the quantitative ion release, the retrieved SBFs were analyzed using inductively coupled plasma mass spectrometry. Two-way ANOVA and Tukey post hoc tests sought the statistical significance of the nickel ion values(p < 0.05). Results In 1 h of immersion, the newly formed structures, exhibiting mostly oxygen signals, were widespread and evident on NiTi surfaces. In contrast, fewer structures were detected on the SS surface in that subgroup. In 7 days of immersion, a tendency for a decrease in the density of the new structures was revealed in NiTi groups. The oxygen signals on NiTi group surfaces significantly increased, contrary to their decrease in SS. Signals of sodium, chlorine, and calcium were detected, indicating salt precipitates in groups. In 30 days of immersion, salt precipitates continued to form. The Ni-ion release values in all instrument groups presented significant differences in comparison to the SBF control in all immersion periods(p < 0.001). No significant differences were observed in immersion time periods or instrument groups(p > 0.05). Conclusions Within the limitations of the presented study, it was concluded that the fractured SS and NiTi root canal instruments release Ni ions in contact with body fluid. However, the Ni ion release values determined during the observation periods are lower than the critical toxic or allergic thresholds defined for the human body. This was due to the ionic dissolution cycle reaching a stable state from 1-hour to 30-day exposure to the body fluid of fractured instruments.